Inheritance and Innovation of Dunhuang Mural Elements in Silk Scarf Design in the Digital Era: The Road to Sustainable Commercialisation of Cultural Heritage - Fei, Liu; Md Yusoff, Irwan Syah; Hj Alli, Hassan Bin (Journal of Neonatal Surgery, 2025)
This study explores how Dunhuang mural elements can be inherited and innovated in silk scarf design in the context of the digital era, and what this process reveals about the sustainable commercialisation of cultural heritage. Through literature review, case study and market research, the study systematically analyses the value of Dunhuang mural elements in contemporary design, the methods of transformation and the role of digital technology in facilitating this process. The results show that digital technology provides a new way for the extraction, reconstruction and innovative application of Dunhuang mural elements, while the design of silk scarves based on Dunhuang elements achieves both cultural heritage and creates considerable economic value. The study proposes a "triple balance" model for the sustainable commercialisation of cultural heritage, which can be useful for the adaptive use of other cultural heritage.